THE STOCK MARKET REACTION TO THE ANNOUNCEMENTTHE OF STOCK SPLIT IN INDONESIA SHARIA STOCK INDEX (ISSI) THE FOR 2013-2018 PERIOD - Salsabiilaa Nadiah Putri Herlambang; Puji Sucia Sukmaningrum (Universitas Airlangga, 2020)
Stock split is a breakdown of the nominal value of stocks into smaller ones carried out by the issuer. This study aims to determine and explain the reaction of the stock market to the announcement of a stock split made by issuers of all sectors in the 2013-2018 Indonesian Sharia Stock Index (ISSI). This study uses a quantitative approach using event studies to analyze market reactions to events. Sampling using purposive sampling and obtained 50 companies and two companies do two stock splits. The sample analysis technique uses the One-Sample Test t-test and Paired Sample t-test with an observation period of 31 days which is 15 days before the announcement of the stock split and 16 days after the announcement of the stock split. The results obtained from this study are that there is no significant abnormal return before the announcement of the stock split, but there is a significant abnormal return after the stock split, although a little. However, there is no significant cumulative average abnormal return as a reaction before or after the stock split. This study also found no significant differences in abnormal returns before and after stock split and changes in cumulative average abnormal returns before and after stock split that was not significant.Keywords: Market Reaction, Stock Split, Average Abnormal Return, Indonesian Sharia Stock Index (ISSI)REFFERENCE Brigham F Eugene dan I.C. Gapenski. (1996). Intermediate financial management, Fifth Edition. New York: The Dryden Press.Brown, S.J. & J.B. Warner. (1985). Using daily stock returns: The case of event studies. Journal of Financial Economics, 14, 3-31.Jogiyanto Hartono. (2009). Teori portofolio dan analisis investasi. Yogyakarta: BPFE.Jogiyanto, Hartono. (2003). Studi peristiwa: Menguji reaksi pasar modal akibat suatu peristiwa. Yogyakarta: BPFE.Jogiyanto, Hartono. (2003). Teori portofolio dan analisis investasi. Yogyakarta: BPFE.Jogiyanto. (2003). Pasar efisien secara keputusan. Jakarta: PT. Gramedia Pustaka Utama.Kementerian Agama RI. (2017). Al Quran dan terjemahannya. Jakarta: Kementerian Agama RI.Otoritas Jasa Keuangan. (2018). Saham syariah (www.ojk.go.id diakses pada 28 September 2018).Subekti, Dwi Agus. (2014). Pengaruh stock split terhadap abnormal return dan volume perdagangan saham (Studi kasus pada perusahaan yang masuk dalam daftar efek syariah periode 2011-2013). Skripsi tidak diterbitkan. Yogyakarta: Universitas Islam Negeri Sunan Kalijaga.Tandelilin, Eduardus. (2007). Analisis investasi dan manajemen portofolio. Yogyakarta: BPFE.